A multi-layered split ring metamaterial for a multiwavelength and tunable lasing spaser - Yan, Changchun (2013)
We report a multiwavelength and tunable lasing spaser realized by a gain-assisted metamaterial. The metamaterial consists of three regularly spaced parallel arrays of weakly asymmetric metallic split rings, with the first-layered array located on the gain medium surface and the other two-layered arrays embedded in it. Our simulations demonstrate that the three-layered metamaterial can radiate three-wavelength electromagnetic waves with high Q factors and transmission enhancement, which can be tuned by varying the gain coefficient.